2019 IFPRI annual report - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
IFPRI’s 2019 Annual Report presents highlights from our research work around the world. Cutting-edge research on climate resilience and sustainability, healthy diets and nutrition, inclusive and efficient food systems, institutions and governance, and rural transformation, as well as cross-cutting work on gender, is helping to inform policies and programs to end hunger and malnutrition.